ANALISIS SISTEM PENAMAAN DAN PENOMORAN BERKAS REKAM MEDIS DI PUSKESMAS RENSING TAHUN 2022 - Yogi Irpani Irmawan; Hary Pristianto (Nusadaya Journal of Multidiciplinary Studies, 2022)
The implementation of the medical record system in the outpatient registration of new patients consists of a filling system and a numbering system. The filling system is a system or method for naming a patient in a medical record file to distinguish one medical record file from another. While the numbering system is a system used to assign numbers to the patient's medical record file. The purpose of preparing this final report is to provide information about the implementation of the naming system and numbering system at the Rensing Health Center. Medical record document is a file containing records of patient identity, examination, treatment, actions and other services to patients in health care facilities. The type of research used is qualitative research with a descriptive approach to phenomenological design. Data collection using interview techniques, observation and study documentation. The sample was obtained by using a random sampling technique. From the results of the practice at the Rensing Health Center, the filling system used according to the rules of the Director General of Health and Medical Affairs (2006), numbering uses a unit system that has been implemented at the Rensing Health Center. The filling system and numbering system at the Rensing Health Center have been implemented but not optimal yet.